Theoretical and simulation analysis of piezoelectric liquid resistance captor filled with pipeline - Li Zheng; Yang Zhigang; Kan Junwu; Lisheng; Yan Bo; Lu Dan (Materials Research Express, 2018)
This paper designs a kind of Piezoelectric liquid resistance capture energy device, by using the superposition theory of the sheet deformation, the calculation model of the displacement curve of the circular piezoelectric vibrator and the power generation capacity under the concentrated load is established. The results show that the radius ratio, thickness ratio and Young’s modulus of the circular piezoelectric vibrator have greater influence on the power generation capacity. When the material of piezoelectric oscillator is determined, the best radius ratio and thickness ratio make the power generation capacity the largest. Excessive or small radius ratio and thickness ratio will reduce the generating capacity and even generate zero power. In addition, the electromechanical equivalent model is established. Equivalent analysis is made by changing the circuit impedance. The results are consistent with the theoretical simulation results, indicating that the established circuit model can truly reflect the characteristics of the theoretical model.